2008
DOI: 10.1210/jc.2008-0350
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long-Term Variations in Serum Calciotropic Hormones after a Single Very Large Dose of Ergocalciferol (Vitamin D2) or Cholecalciferol (Vitamin D3) in the Elderly

Abstract: Cholecalciferol is almost twice as potent as ergocalciferol in increasing serum 25(OH)D, when administered either by mouth or im. 25(OH)D plays a role in modulating serum PTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
202
0
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(239 citation statements)
references
References 38 publications
25
202
0
9
Order By: Relevance
“…As regards the literature cited by Dr Roth, the report by Armas et al (2004) was a study of serum 25-hydroxyvitamin D (25(OH)D) till only 1 month after vitamin D dosing, but not longer. The study by Ilahi et al (2008) (and also by Romagnoli et al, 2008) is useful to illustrate the pharmacokinetics of 25(OH)D after administration of a single oral large dose of vitamin D3, and we agree with their suggestion that the levels of 25(OH)D are maintained above baseline for a little beyond 2 months after an oral dose. These results were published only when our study was almost complete.…”
Section: Conflict Of Interestsupporting
confidence: 79%
“…As regards the literature cited by Dr Roth, the report by Armas et al (2004) was a study of serum 25-hydroxyvitamin D (25(OH)D) till only 1 month after vitamin D dosing, but not longer. The study by Ilahi et al (2008) (and also by Romagnoli et al, 2008) is useful to illustrate the pharmacokinetics of 25(OH)D after administration of a single oral large dose of vitamin D3, and we agree with their suggestion that the levels of 25(OH)D are maintained above baseline for a little beyond 2 months after an oral dose. These results were published only when our study was almost complete.…”
Section: Conflict Of Interestsupporting
confidence: 79%
“…Ish-Shalom et al 45 documented a rise in both serum 25(OH)D and 1,25(OH)2D concentrations 1 day following a single dose of 1.125 mg of vitamin D3, but these changes were not accompanied by a rise in serum [Ca]. Ilahi et al 46 found that serum [Ca] did not rise in the first 5 days following a single vitamin D3 dose of 2.5 mg, and Romagnoli et al 47 likewise did not find any increase in serum [Ca] after administering 7.5 mg (E Romagnoli, personal communication). However, Cipriani et al 48 recently reported that a single bolus vitamin D3 dose of 15 mg in young adults induced a significant increase in the mean serum calcium concentration on day 3, coincident with a peak mean 1,25(OH)2D concentration.…”
Section: -Hydroxyvitamin D ([25(oh)d]mentioning
confidence: 99%
“…Nous nous basons pour cela sur des études qui ont montré que, pour une même dose administrée, la vitamine D 3 permettait de maintenir la 25OHD élevée plus longtemps que la vitamine D2 [90][91][92]. Nous devons toutefois signaler que cela n'a pas été retrouvé par toutes les équipes [93].…”
Section: éTapeunclassified